Calculus gems brief lives and memorable mathematics - Simmons George F (Washington Mathematical Association of America, 2007)
The first half of Calculus Gems is a biographical history of mathematics from the earliest times to the late nineteenth century. The author shows how science - and mathematics in particular - is something that people do, and not merely a mass of observed
Keywords: Biographies; Calculus-history; Mathematicians; Mathematics-history